2021
DOI: 10.3390/en14123526
|View full text |Cite
|
Sign up to set email alerts
|

Bushfire: Retrofitting Rural and Urban Fringe Structures—Implications of Current Engineering Data

Abstract: Since the 2009 Black Saturday bushfires in which 173 lives were lost, two-thirds of whom died in their homes, the question of what a home prepared for bushfire looks like has been repeatedly raised. The 2019/2020 fires saw us not much further advanced. This paper seeks to consolidate what is known about bushfire behavior, its influence upon structures, and, through this data, infer improved standards of practice for retrofitting rural and urban fringe homes. In particular, the prevention of ember and smoke inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The eleventh paper, "Bushfire: retrofitting rural and urban fringe structures", Ref. [12] reviews extant research on bushfire behavior and its impact on residential structures. As a consequence of global warming, Australia and other parts of the world increasingly suffer from the devastation of bushfires.…”
Section: Special Issue Contentmentioning
confidence: 99%
“…The eleventh paper, "Bushfire: retrofitting rural and urban fringe structures", Ref. [12] reviews extant research on bushfire behavior and its impact on residential structures. As a consequence of global warming, Australia and other parts of the world increasingly suffer from the devastation of bushfires.…”
Section: Special Issue Contentmentioning
confidence: 99%
“…Research into the cause of bushfire destruction of homes has demonstrated that fire damage is magnified by the proximity of buildings and secondary structures, whereby fires, through ember attack, radiant heat or flame, can travel from one structure to another (Blanchi and Leonard 2005). Given the complexities that relate to property loss associated with bushfires, few studies offer any clear statistical relationship between the inter-structure proximity and loss (Costin 2021) while greater research attention has focused on the proximity of a structure and bushland. Roberts et al (2021) modelled the effects of embers on property loss.…”
Section: Introductionmentioning
confidence: 99%